Non-Uniform Spatial Dose Distributions Around Co-60 in Human Tissue for Brachytherapy Treatment using Monte Carlo EGS Code - Ibrahim Othman,; Bsher Abour,; Zedan Alsnosi, (AlQalam Journal of Medical and Applied Sciences, 2022)
Brachytherapy (BT) uses encapsulated radioactive sources to deliver low (LDR) or high (HDR) dose rates to tissues. The source is implanted interstitial into tissues such as the radioactive needles used in the treatment of tongue carcinoma. These sources must be calibrated to accepted standards. In previous work, we used Monte Carlo Electron Gamma Shower EGS Code for simulating the use of Ir-192 source capsule interstitial in tongue within the oral cavity. In the present work, we extended the simulation to Co-60 source capsule which, for simplification, is similar in structure and surroundings to the Ir-192 one. Radiation Data analysis and spatial Dose distributions are presented. Simulations of non-uniform dose distributions in both the source capsule and the surroundings were presented. Data preparation and examinations of the source capsule details were carried out and compared with the published data. Both depth and radial dose curves are also analyzed. The results showed that Monte Carlo EGS is practically applicable to dose distribution estimate around brachytherapy source applicators. The dose distributions are maximum around the source and fall to minimum rapidly in the near tissue that could be adjusted for the chosen dose value. Comparisons with Ir-192 are one of our objectives in future investigation.